Bentuk dan Fungsi Tari Telek Melampahan di Nusa Lembongan - Ni Nyoman Kasih; Luh Risa Melliani; Dyah Kustiyanti (Journal on Education, 2023)
Telek Melampahan Dance is one of the sacred dances originating from Lembongan Village. This dance was created by Alm. I Wayan Rawit because of a pawesik from relatives in Nusa Lembongan. This dance is danced every 6 months during Kuningan Day. This research that focuses on the Telek Melampahan Dance in Lembongan Village has 2 problems with the main study, namely (1) How does the Telek Melampahan Dance form in Nusa Lembongan, (2) How does the Telek Melampahan Dance function in Nusa Lembongan. The theory used to dissect the two problems is the aesthetic theory by Djelantik and the functional theory by Soedarsono and Sumandiyo Hadi. This research is a qualitative descriptive study in terms of performing arts studies using interview data collection techniques, observation, documentation and literature study. The results of this study indicate that this dance is different from the Telek Dance in general. The Telek Melampahan Dance is inspired by the Telek Jumpai Dance in Klungkung. The performance takes the story from the Lontar Nandha tattwa with an even number of Telek dancers, 2 jauk dancers and 5 dancers of Pura Dalem figures (Barong, Rarung, Baka, and Sang Hyang Baerawi). Judging from the variety of movements and clothing used, it is still very simple. The place where it is performed is also different from the Telek Dance in general which is danced in temples, but this dance is danced at Catus Pata in Lembongan Village. This dance was created with a function as a ritual means of repelling reinforcements. Before this dance is performed, stakeholders will offer offerings in the form of segehan, pejati and pemmbleh at Catus Pata, Lembongan Village. In addition, this dance can also be said as a means of communication to build solidarity for the people of Lembongan Village.